Analysis Of Positive Legal Arrangements Against Minority Shareholders Suing The Company's Board Of Directors For Actions That Resulted In The Loss Of The Company's Funds - Simon Alex Pasaribu; Hulman Panjaitan; Paltiada Saragi (PALAR | PAKUAN LAW REVIEW, 2026)
This study analyzes the regulation of minority shareholders’ legal standing to sue company directors and examines the standards of directors’ civil liability for corporate financial losses under Indonesian positive law. The research aims to clarify the scope of legal protection available to minority shareholders and to evaluate how fiduciary principles and the business judgment rule are applied in corporate governance disputes. This research employs a normative juridical method using statutory, analytical, case, and comparative approaches. The primary legal framework is based on Law No. 40 of 2007 on Limited Liability Companies and related governance regulations, supported by doctrinal and jurisprudential analysis. The findings show that Indonesian company law formally recognizes derivative and direct actions as mechanisms for minority shareholder protection, but their effectiveness is limited by procedural barriers, evidentiary burdens, and information asymmetry. Directors’ civil liability is grounded in fiduciary duties, particularly the duty of care and duty of loyalty, while the statutory formulation of the business judgment rule provides conditional protection for good-faith managerial decisions. The study concludes that although the legal framework seeks to balance accountability and managerial discretion, clearer procedural standards and stronger enforcement mechanisms are needed to enhance minority shareholder protection and legal certainty. Keywords: minority shareholders; directors’ liability; fiduciary duty; business judgment rule; corporate governance.